Prevalence of recurrent pathogenic microdeletions and microduplications in over 9500 pregnancies. (24th June 2015) - Grati, Francesca Romana; Molina Gomes, Denise; Ferreira, Jose Carlos Pinto B.; Dupont, Celine; Alesi, Viola; Gouas, Laetitia; Horelli‐Kuitunen, Nina; Choy, Kwong Wai; García‐Herrero, Sandra; de la Vega, Alberto Gonzalez; Piotrowski, Krzysztof; Genesio, Rita; et al.
Abstract Objectives The implementation of chromosomal microarray analysis (CMA) in prenatal testing for all patients has not achieved a consensus. Technical alternatives such as Prenatal BACs‐on‐BeadsTM (PNBoBsTM) have thus been applied. The aim of this study was to provide the frequencies of the submicroscopic defects detectable by PNBoBsTM under different prenatal indications. Methods A total of 9648 prenatal samples were prospectively analyzed by karyotyping plus PNBoBsTM and classified by prenatal indication. The frequencies of the genomic defects and their 95%CIs were calculated for each indication. Results The overall incidence of cryptic imbalances was 0.7%. The majority involved the DiGeorge syndrome critical region (DGS). The additional diagnostic yield of PNBoBsTM in the population with a low a priori risk was 1/298. The prevalences of DGS microdeletion and microduplication in the low‐risk population were 1/992 and 1/850, respectively. Conclusions The constant a priori risk for common pathogenic cryptic imbalances detected by this technology is estimated to be ~0.3%. A prevalence higher than that previously estimated was found for the 22q11.2 microdeletion. Their frequencies were independent of maternal age. These data have implications for cell‐free DNA screening tests design and justify prenatal screening for 22q11 deletion, as early recognition of DGS improves its prognosis. © 2015 John Wiley & Sons, Ltd.